The Electrochemical Characteristics and Applicability of an Amorphous Sulfide-Based Solid Ion Conductor for the Next-Generation Solid-State Lithium Secondary Batteries - Aihara, Yuichi; Ito, Seitaro; Omoda, Ryo; Yamada, Takanobu; Fujiki, Satoshi; Watanabe, Taku; Park, Youngsin; Doo, Seokgwang (Frontiers in Energy Research, 2016)
Sulfide based solid electrolytes are of considerable practical interest for all solid-state batteries due to their high ionic conductivity and softness at room temperature. In particular, iodine containing lithium thiophosphate is known to exhibit high ionic conductivity but its applicability in solid-state battery remains to be examined. To demonstrate the possibility of the iodine doped solid electrolyte (SE), LiI-Li3PS4 was used to construct two different types of test cells were prepared, Li/SE/S and Li/SE/LiNi0.80Co0.15Al0.05 cells. The solid electrolyte, LiI-Li3PS4 showed a high ionic conductivity approximately 1.2 mScm-1 at 25 ℃. Within 100 cycles, the capacity retention was better in Li/SE/S cell, and the red-ox shuttle was not observed due to physical blockage of SE layer. The capacity fade was approximately 4% from the maximum capacity observed at 10th cycle, after 100 cycles in Li/SE/S cell. On the contrary, the capacity fade was much larger in Li/SE/LiNi0.80Co0.15Al0.05 cell, probably due to the decomposition of the electrolyte at the operating potential range. Nevertheless, both the Li/SE/LiNi0.80Co0.15Al0.05 and Li/SE/S cells exhibited the high coulombic efficiencies above 99.6% and 99.9% during charge-discharge cycle test, respectively. This fact indicates that a high energy density can be possible without an excess lithium metal anode. In addition, it was particularly interesting that the SE showed a reversible capacity about 260 mAhg-1-SE. This electrolyte may have not only as a role of the ion conduction, but also as a catholite.